PENYELESAIAN PERSAMAAN POISSON MENGGUNAKAN METODE HOMOTOPI PERTUBASI - Mashuri Mashuri; Sulistiowati Nur Rahmi; Marwah Daud Wijayanti; Alviana Pratama Putri (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
In this paper, we discuss the solution of the Poisson equation with some initial condition. We use the homotopy pertubation method to get the solution.. The homotopy pertubation method is a combination of the homotopy method and the pertubation method. The solution of the equation is assumed to be in the form of a power series. The result is by using the homotopy pertubation method for the diffution equation, the solution is the same with the exact solution.